The Cuban Strategy for Combatting the COVID-19 Pandemic - Perez Riverol, Amilcar [UNESP] (Medicc-med Educ Cooperation Cuba, 2020)
The emerging SARS-CoV-2, a novel human coronavirus, caused the COVID-19 pandemic, with more than 9.5 million cases and 484 000 known fatalities to date (June 24th, 2020). In several regions, healthcare systems have collapsed whereas interventions applied to slow the viral spreading have had major social and economic impacts. After China, Europe, and the United States, Latin America has emerged as the new epicenter of the pandemic. By late-June, the region accounted for roughly 50% of global daily deaths (Gardner, 2020). The evolution of the COVID-19 pandemic in the region has been heterogenous as several countries are currently experiencing exponential growth of their daily cases and fatalities, while others have successfully controlled their corresponding outbreaks. Cuba confirmed its first COVID-19 cases in mid-March. After a three-month outbreak, the country recently began to move to a post epidemic phase. This dispatch details some relevant aspects of the strategy deployed in Cuba to face the COVID-19 pandemic and to decrease the impact of this emerging disease in the country. In addition, it describes the evolution of some epidemiological variables which allowed the country to de-escalate some of the non-pharmaceutical interventions applied during the outbreak.